The role of successive Iraqi Governments in managing Cultural diversity/ Analytical study - أ.د.; Rese. , الباحث (lark, 2024)
The issue of cultural diversity in societies is one of the important issues and it is not a new issue, there is hardly a society without it, and the issue of cultural diversity is not a problem in itself, but the management of this diversity has grown  and the mechanisms used in this management are what cause social tensions, and this is what we dealt with in this research as we shed light on the management of each of the successive governments and its method of managing cultural diversity in Iraqi society, and the  extent of the impact of each of these governments on The social structure, and we dealt with the nature of the responses of successive governments to the demands of legitimate cultural groups,  and how they dealt with them, in order to build a perception of the role of those  governments that have ruled Iraq since the establishment of the Iraqi state, as well as knowing the role of diverse cultural groups in responding to  the policies of those Governments, and the nature of the relationship between diverse cultural groups and successive governments that ruled Iraq using  the inductive analytical  method. We reached several research conclusions, including:1- Most of the political elites that successively ruled Iraq lack the element of rationality, and there is no effective and sound relationship between most of these political elites and society, if an effective and sound relationship is available, this will make the political system more legitimate.2- The weak political performance of most political systems and in various periods, so they could not absorb societal diversity and manage it properly.3- The process of managing cultural diversity is one of the most difficult tasks that requires intensifying efforts by political systems to reach social integration, consensus and effectiveness between political elites and cultural groups.We have made some proposals, which may address some problems, including:1- Urging the current Iraqi government to take the necessary measures to activate the rights of cultural diversity, and to treat all the Iraqi people in full swing without discrimination between any of them.2- Include in the educational curricula at various stages clear references to the existence of other components living in Iraq,  and introduce their history, literature and culture.3- Activating real national reconciliation, and what we mean by real reconciliation is that the institutions of government are the initiative or not in putting forward rapprochement projects and lifting cases of discrimination in all its forms.
Keywords: Cultural diversity, Ethnic minorities, the Iraqi state, Sociology.